Women Entrepreneurship in SMEs: A Review of Challenges, Opportunities, and Policy Implications - Ritu Wadhwani; Nidhi Mahajan (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2026)
Women entrepreneurship has gained increasing attention as a significant contributor to economic growth, innovation, and social development. Small and medium-sized enterprises (SMEs) constitute a vital component of national economies and provide a platform for women to participate actively in entrepreneurial activities. Despite the growing involvement of women in business ventures, women entrepreneurs often encounter multiple barriers that hinder their entrepreneurial success. These challenges include limited access to financial resources, gender-based discrimination, lack of managerial skills, inadequate support networks, and socio-cultural constraints. At the same time, emerging opportunities such as digital technologies, supportive government policies, and entrepreneurial ecosystems are enabling women entrepreneurs to expand their business activities. This review article synthesizes existing literature on women entrepreneurship in SMEs by examining the major challenges faced by women entrepreneurs, identifying opportunities for growth, and discussing policy implications for fostering inclusive entrepreneurial ecosystems. The study highlights the need for gender-sensitive policies, improved access to finance, entrepreneurial education, and institutional support to promote sustainable women-led enterprises. The findings provide valuable insights for researchers, policymakers, and practitioners interested in promoting women entrepreneurship and strengthening SME development.